Migratory route of Strongyloides venezuelensis in Lewis rats: Comparison of histological analyses and PCR - Marra, Nelson Mendes [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Machado, Gabriel Capella [UNESP]; Goncalves Zorzella-Pezavento, Sofia Fernanda [UNESP]; Donega Franca, Thais Graziela [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Amarante, Alessandro Francisco Talamini do [UNESP]; Sartori, Alexandrina [UNESP]; Amarante, Monica R. V. [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Strongyloides venezuelensis is a parasitic nematode that has been used as a model to study human and animal strongyloidiasis. In this study, we compared the sensitivity between traditional methodologies and PCR assay to characterize the dynamics of S. venezuelensis infection and its migration route in Lewis rats subcutaneously infected with 4000 L3. The dynamics of the infection was determined by counting the number of eggs and by detecting parasite deoxyribonucleic acid in faeces samples. Both techniques similarly detected the infection at day 6 after larvae inoculation. However. PCR performed with the genus primer showed higher sensitivity during the recovery phase. Histological analysis and PCR assay were then used to follow parasite tissue migration. S. venezuelensis migration route included the muscular fibers below the skin, the pulmonary alveoli and the small intestine vilosities. The sensitivity of these two techniques to detect parasite's presence in these tissues was statistically similar. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Strongyloides venezuelensis; Migratory route; Lewis rats; Histological analysis; PCR